2017
DOI: 10.1002/qj.3063
|View full text |Cite
|
Sign up to set email alerts
|

Scale‐selective dissipation in energy‐conserving finite‐element schemes for two‐dimensional turbulence

Abstract: We analyze the multiscale properties of energy‐conserving upwind‐stabilized finite‐element discretizations of the two‐dimensional incompressible Euler equations. We focus our attention on two particular methods: the Lie derivative discretization introduced by Natale and Cotter and the Streamline Upwind/Petrov–Galerkin (SUPG) discretization of the vorticity advection equation. Such discretizations provide control on enstrophy by modelling different types of scale interactions. We quantify the performance of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…In our case, the upwinding in the velocity field u also dissipates enstrophy, with little difference in the dissipation rate whether or not upwinding in D is also included in the discretisation (see image 7). More details on the dissipation of enstrophy depending on the choice of upwinding can be found in [16].…”
Section: 9)mentioning
confidence: 99%
“…In our case, the upwinding in the velocity field u also dissipates enstrophy, with little difference in the dissipation rate whether or not upwinding in D is also included in the discretisation (see image 7). More details on the dissipation of enstrophy depending on the choice of upwinding can be found in [16].…”
Section: 9)mentioning
confidence: 99%
“…which is precisely the correct time derivative term. Applying this approach and using functional derivatives (65) - (67) Due to the choice of spaces, (77) holds pointwise, not just in an integral sense. Additionally, (65) can be directly substituted into (78), leaving only the auxiliary equations (66) and (67) to be solved.…”
Section: Discrete Equations Of Motionmentioning
confidence: 99%
“…Since this test function is applied to the entire equation, this does not alter the residual formulation, only the nature of the test functions, and hence the scheme is expected to remain consistent at the appropriate order. SUPG was first applied to the Euler equations in streamfunction-vorticity formulation by Tezduyar et al (1988); Tezduyar (1989), and the multiscale behaviour of the resulting scheme was examined by Natale and Cotter (2017). The SUPG modification of the energy-enstrophy conserved shallow water scheme of this paper is obtained by replacing q δ in Equation (51) by q * given by…”
Section: Energy-conserving Enstrophy-dissipating Schemementioning
confidence: 99%
“…Eldred et al (2016) constructed compatible spaces from splines that allow higher-order approximations constructed around the low-order C-grid data structure, and Lee et al (2017) used mimetic spectral elements. In the context of imcompressible two-dimensional turbulence, Natale and Cotter (2017) considered consistent energy-conserving/enstrophy-dissipating finite element schemes, including a formulation that extends to a consistent energy-conserving enstrophy-dissipating version of the McRae and Cotter (2014) scheme, and showed that these schemes have favourable turbulent backscatter properties.…”
Section: Introductionmentioning
confidence: 99%